2014
DOI: 10.1093/deafed/enu018
|View full text |Cite
|
Sign up to set email alerts
|

Can Mild Bilateral Sensorineural Hearing Loss Affect Developmental Abilities in Younger School-Age Children?

Abstract: The research study was conducted for the purpose of examining the influence of mild bilateral sensorineural hearing loss (MBSNHL) on developmental abilities of younger school-age children. The sample encompassed 144 children with MBSNHL, aged 7.5-11 (M = 8.85). MBSNHL (20-40 dB HL) was identified by pure tone audiometry. The control group encompassed 160 children with normal hearing. The Acadia test of developmental abilities was used for assessment of developmental abilities. Although statistically significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 32 publications
1
12
0
1
Order By: Relevance
“…This finding is consistent with results from the OCHL cohort as a whole: Another report on the entire sample of children who are hard of hearing showed a pattern of children performing, on average, within the normative range of the standardized tests but significantly lower than the OCHL control group with normal hearing . This pattern reflects an issue that has been discussed by other authors in the literature on mild HL (Blair et al, 1985;Đoković et al, 2014;Kiese-Himmel & Ohlwein, 2003), in which children with mild HL performed within normal limits on standardized language measures but significantly worse when compared with peers. In the present study, we made comparisons within the group of children with mild HL, but the end result is similar.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…This finding is consistent with results from the OCHL cohort as a whole: Another report on the entire sample of children who are hard of hearing showed a pattern of children performing, on average, within the normative range of the standardized tests but significantly lower than the OCHL control group with normal hearing . This pattern reflects an issue that has been discussed by other authors in the literature on mild HL (Blair et al, 1985;Đoković et al, 2014;Kiese-Himmel & Ohlwein, 2003), in which children with mild HL performed within normal limits on standardized language measures but significantly worse when compared with peers. In the present study, we made comparisons within the group of children with mild HL, but the end result is similar.…”
Section: Discussionsupporting
confidence: 77%
“…Furthermore, there is ambiguity regarding appropriate clinical interventions for children with mild HL, particularly involving the need for audiological management (Fitzpatrick, Durieux-Smith, & Whittingham, 2010). This general uncertainty exists, at least in part, because of conflicting findings from the past and present literature: Some studies have reported negative effects of mild HL on developmental outcomes (Davis, Stelmachowicz, Shepard, & Gorga, 1981;Đoković et al, 2014), whereas other studies have suggested that mild HL has minimal or no effect on outcomes (Kiese-Himmel & Ohlwein, 2003;Porter, Sladen, Ampah, Rothpletz, & Bess, 2013;Wake et al, 2006). Limitations in past studies include grouping children with mild and unilateral HL together under the umbrella term of minimal HL and/or failing to consider the contributions of early intervention, aided audibility, or consistent hearing aid (HA) use to outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the limited research that does exist provides mixed evidence regarding the negative impact of mild HL on outcomes. Although some authors have concluded that children with mild HL do not experience adverse effects as the result of HL in this range (e.g., Kiese-Himmel & Ohlwein, 2003;Wake et al, 2006;Wolgemuth, Kamhi, & Lee, 1998), other studies have indicated that these children face challenges at home and school (e.g., Blair et al, 1985;Đoković et al, 2014;Porter, Sladen, Ampah, Rothpletz, & Bess, 2013). For example, Wake et al (2006) did not find significant differences between children with mild HL and children with normal hearing on measures of reading, language, and behavior.…”
Section: Developmental Outcomes and Service Provision In Children Witmentioning
confidence: 97%
“…It should be noted, however, that there are limitations in interpreting these prior studies with regard to the importance of early identification and intervention for children with mild HL. Much of the available research was conducted with populations of children who did not have access to NHS, and thus the children were identified later, on average, than might be expected for children with mild HL born in the post-NHS era (Blair et al, 1985;Davis et al, 1986;Đoković et al, 2014;Wake et al, 2006;Wolgemuth et al, 1998).…”
Section: Developmental Outcomes and Service Provision In Children Witmentioning
confidence: 99%
“…More pertinent to the OCHL study sample are studies that examined the consequences of mild bilateral sensorineural HL. Dokovic et al (2014) identified 144 school-aged children with mild bilateral HL who had not previously received HAs or other services. These students demonstrated deficits in phonological memory and morphosyntactic skills, suggesting consequences for structural aspects of language when mild HL goes untreated.…”
Section: Introductionmentioning
confidence: 99%